2011
DOI: 10.1021/cb100284d
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Labeling of Fucosylated Glycans in Developing Zebrafish

Abstract: Many developmental processes depend on proper fucosylation, but this post-translational modification is difficult to monitor in vivo. Here we applied a chemical reporter strategy to visualize fucosylated glycans in developing zebrafish. Using azide-derivatized analogues of fucose, we metabolically labeled cell-surface glycans and then detected the incorporated azides via copper-free click chemistry with a difluorinated cyclooctyne probe. We found that the fucose salvage pathway enzymes are expressed during zeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 35 publications
0
81
0
1
Order By: Relevance
“…Previous studies have shown that fucosylation progressively accumulates through the first four days of early zebrafish development (Dehnert et al, 2011). Limiting fucosylation in mice is known to cause developmental defects including early embryonic death (Du et al, 2010; Smith et al, 2002), neuronal migration disorders (Ohata et al, 2009), skeletal abnormalities and other defects (Hayes et al, 2013; Ma et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that fucosylation progressively accumulates through the first four days of early zebrafish development (Dehnert et al, 2011). Limiting fucosylation in mice is known to cause developmental defects including early embryonic death (Du et al, 2010; Smith et al, 2002), neuronal migration disorders (Ohata et al, 2009), skeletal abnormalities and other defects (Hayes et al, 2013; Ma et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Chemical reporter strategies have been applied to visualize glycans in cells and living organisms with success (18)(19)(20)(21)(22)(23)(24)(25), however, insights into the functional relevance of glycans in normal and disease biology have yet to emerge from these applications. Our findings pave the way for the use of chemical reporter strategies to study the impact of altered glycosylation on the pathophysiology of human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It can be tagged by Staudinger ligation using modified phosphines, by a copper (I)-catalyzed cycloaddition with terminal alkynes (CuAAC), or by a strain-promoted alkyne-azide cycloaddition (SPAAC) using cyclooctynes (20,21). Such chemical reporter strategies can be used to monitor the trafficking of glycans within cells and to localize the expression of specific classes of glycans within living organisms, such as developing zebrafish embryos or Caenorhabditis elegans (21)(22)(23)(24)(25). Insights into the functional relevance of glycans in normal and disease biology have yet to emerge from these technologies, however.…”
mentioning
confidence: 99%
“…On the other hand, Bertozzi and coworkers (19)(20)(21)(22) metabolically introduced monosaccharidebased chemical reporters-N-acyl derivatives of ManNAc, N-acetyl-D-glucosamine, or N-acetyl-D-galactosamine containing a ketone or azide group-onto cellular surface glycans followed by bioorthogonal, chemoselective coupling with a fluorescent dye or an affinity tag bearing hydrazide/aminooxy (for ketones) or phosphine/alkyne (for azides) group. This elegant methodology, combining metabolic engineering and bioorthogonal reactions, enabled in situ imaging or proteomic enrichment of one glycan type (19)(20)(21)(22) and has been applied to many different cell lines (e.g., Jurkat, HeLa, CHO, and neuron-like blastoma cells) and organisms (e.g., zebrafish, mice, and microbes) for the selective labeling of sialic acid (23)(24)(25), N-acetyl-D-galactosamine residue (in mucin-type O-linked glycan) (26)(27)(28), fucose residue (29)(30)(31)(32), and LPSs/O-antigen (33,34). Although there are innumerable previous reports, the metabolic labeling and the imaging of glycan structures in primary neurons have yet to be achieved, although the surface glycans, especially PSA-NCAMs, play important roles in neuronal development.…”
Section: Significancementioning
confidence: 99%